2022
DOI: 10.1093/rheumatology/keac305
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination-related adverse events among autoimmune disease patients: results from the COVAD study

Abstract: Objectives COVID-19 vaccines have been proven to be safe in the healthy population. However, gaps remain in the evidence of their safety in patients with systemic autoimmune and inflammatory disorders (SAIDs). COVID-19 vaccination related adverse events (ADEs) in patients with SAIDs and healthy controls (HC) seven days post-vaccination were assessed in the COVAD study, a patient self-reported cross-sectional survey. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…We have recently reported vaccine safety in idiopathic inflammatory myopathies (IIMs) using data from the global COVID-19 vaccination in autoimmune diseases (COVAD) study initiative, demonstrating the overall benefit of vaccination in this group of individuals (7,8). However, in this study, we observed a greater predisposition to specific adverse events, such as skin rashes in certain IIM subgroups, particularly the dermatomyositis subgroup and those with active inflammatory disease, such as the inclusion body myositis subgroup (7).…”
Section: Introductionmentioning
confidence: 53%
“…We have recently reported vaccine safety in idiopathic inflammatory myopathies (IIMs) using data from the global COVID-19 vaccination in autoimmune diseases (COVAD) study initiative, demonstrating the overall benefit of vaccination in this group of individuals (7,8). However, in this study, we observed a greater predisposition to specific adverse events, such as skin rashes in certain IIM subgroups, particularly the dermatomyositis subgroup and those with active inflammatory disease, such as the inclusion body myositis subgroup (7).…”
Section: Introductionmentioning
confidence: 53%
“…Some studies evaluated the specific patient concerns related to the COVID-19 vaccine, which included unknown long-term side effects, the newness of the COVID-19 vaccine, and the perception of rushed development and introduction with potential financial links to the pharmaceutical companies ( 9 , 18 , 24 , 26 ). Those unvaccinated also feared that the vaccine would be harmful and could cause thrombosis ( 24 ), despite well-documented contrary evidence ( 43 ). Furthermore, a concern about potential side effects is a well-documented primary argument against COVID-19 vaccination among the general Polish population ( 3 ) and health care workers, especially nurses ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…An 82 year old woman with signs of general discomfort and body pain after a week of receiving the vaccine was the first case that showed the association between the GBS and vaccination [130] . In addition, clinical signs related to the GBS and the vaccines from Janssen and ChAdOx1-S/nCoV-19 were observed in India and England [130] , [131] .…”
Section: Increased Risk Of Autoimmune Diseases Related To Covid-19mentioning
confidence: 99%